(untitled) (Archives of Clinical Psychiatry, 2009)
These practice guidelines for the biological treatment of unipolar depressive disorders were developed by an international Task Force of the World Federation of Societies of Biological Psychiatry (WFSBP). The goal for developing these guidelines was to systematically review all available evidence pertaining to the treatment of the complete spectrum of unipolar depressive disorders, and to produce a series of practice recommendations that are clinically and scientifically meaningful based on the available evidence. These guidelines are intended for use by all physicians seeing and treating patients with these conditions. The data used for developing these guidelines have been extracted primarily from various national treatment guidelines and panels for depressive disorders, as well as from meta-analyses and reviews on the efficacy of antidepressant medications and other biological treatment interventions identified by a search of the MEDLINE database and Cochrane Library. The identified literature was evaluated with respect to the strength of evidence for its efficacy and was then categorized into four levels of evidence (A-D). The first part of these WFSBP guidelines on unipolar depressive disorders covered the acute and continuation treatment of major depressive disorder (Bauer et al., 2002). This second part of the guidelines covers the management of the maintenance-phase treatment of major depressive disorder, as well as the treatment of chronic and subthreshold depressive disorders (dysthymic disorder, double depression, minor depressive disorder and recurrent brief depression). These guidelines are primarily concerned with thebiological treatment (including antidepressants, lithium, other psychopharmacological and hormonal medications, and electroconvulsive therapy) of young adults and also, albeit to a lesser extent, children, adolescents and older adults.